Exposure Assessment for Italian Population Groups to Deoxynivalenol Deriving from Pasta Consumption - Carlo Brera; Valentina Bertazzoni; Francesca Debegnach; Emanuela Gregori; Elisabetta Prantera; Barbara De Santis (Toxins, 2013)
Four hundred and seventy-two pasta samples were collected from long retail distribution chain sales points located in North, Central and South Italy. Representative criteria in the sample collection were followed in terms of number of samples collected, market share, and types of pasta. Samples were analysed by an accredited HPLC-UV method of analysis. The mean contamination level (64.8 μg/kg) of deoxynivalenol (DON) was  in the 95th percentile (239 μg/kg) and 99th percentile (337 μg/kg), far below the legal limit (750 μg/kg) set by Regulation EC/1126/2007, accounting for about one tenth, one third and half the legal limit, respectively. Ninety-nine percent of samples fell below half the legal limit. On the basis of the obtained occurrence levels and considering the consumption rates reported by the Italian official database, no health concern was assessed for all consumer groups, being that exposure was far below the Tolerable Daily Intake (TDI) of 1000 ng/kg b.w/day. Nevertheless, despite this, particular attention should be devoted to the exposure to DON by high consumers, such as children aged 3–5 years, who could reach the TDI even with very low levels of DON contamination.